2019
DOI: 10.1021/jacs.9b04275
|View full text |Cite
|
Sign up to set email alerts
|

Scandium-Catalyzed Regio- and Stereoselective Cyclopolymerization of Functionalized α,ω-Dienes and Copolymerization with Ethylene

Abstract: The precise control of regio- and stereochemistry in the cyclopolymerization of heteroatom-functionalized α,ω-dienes is of much interest and importance, but has remained a challenge to date. We report herein the regio-, diastereoselective and stereoregular cyclopolymerization of ether- and thioether-functionalized 1,6-heptadienes by a half-sandwich scandium catalyst. The polymerization of 4-benzyloxy-1,6-heptadiene selectively afforded the corresponding benzyloxy-functionalized cyclic polymer composed of 1,2,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 65 publications
2
50
0
Order By: Relevance
“…We have recently found that the interaction of heteroatom (O, N, or S) with rare‐earth‐metal catalysts can efficiently promote various unique chemical transformations, including the (co)polymerization of functionalized olefins, such as the syndiospecific polymerization of heteroatom‐containing α‐olefins, the regio‐ and stereoselective cyclopolymerization of functionalized α,ω‐dienes and the alternating copolymerization of anisyl‐functionalized propylenes with ethylene . These findings have promoted us to explore the potential of rare‐earth catalysts for the stereospecific, sequence‐controlled copolymerization of prochiral polar and non‐polar olefins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently found that the interaction of heteroatom (O, N, or S) with rare‐earth‐metal catalysts can efficiently promote various unique chemical transformations, including the (co)polymerization of functionalized olefins, such as the syndiospecific polymerization of heteroatom‐containing α‐olefins, the regio‐ and stereoselective cyclopolymerization of functionalized α,ω‐dienes and the alternating copolymerization of anisyl‐functionalized propylenes with ethylene . These findings have promoted us to explore the potential of rare‐earth catalysts for the stereospecific, sequence‐controlled copolymerization of prochiral polar and non‐polar olefins.…”
Section: Methodsmentioning
confidence: 99%
“…The coordination of FP to the catalyst is favored over that of St, because of the strong interaction of the FG unit in FP with the rare‐earth metal atom. Such interaction may bring the C=C bond in FP to coordinate to the metal atom in a si ‐configuration ( si ‐A) . The subsequent 2,1‐insertion of the C=C bond into the Ln‐CH 2 C 6 H 4 NMe 2 ‐ o bond should generate an intermediate like ( S )‐B.…”
Section: Methodsmentioning
confidence: 99%
“…Hou also reported the regio‐, diastereoselective, and stereoregular cyclopolymerization of ether‐ and thioether‐functionalized 1,6‐heptadienes + ethylene with Sc‐3 (Figure ). Thus, polymerization of 4‐benzyloxy‐1,6‐heptadiene selectively affords a polymer composed of 1,2,4‐ cis ‐substituted‐ethylene‐cyclopentane (ECP) microstructures arrayed in an isospecific fashion (95 % mmm ).…”
Section: Group 3 Catalystsmentioning
confidence: 98%
“…Furthermore, Arnold and coworkers have synthesized a homolytic Sc complex containing three equiv. of alkoxo-tethered NHCs (Alko-NHC), Sc(Alko-NHC) 3 (30), via the treatment of ScCl 3 (THF) 3 with the potassium salt of Alko-NHC ( Figure 9) [60]. Complex 30 exhibited frustrated-Lewis-pair type behavior that could activate three equivalents of CO 2 via the Sc-C(NHC) bond.…”
Section: Rare Earth Catalysts Containing a Heteroatom-tethered Nhc LImentioning
confidence: 99%
“…The development of Ln catalysts for polymerization has attracted a considerable amount of attention in recent decades [16,17]. Compared with transition metal catalysts, Ln complexes are considered to have unique advantages in the coordination polymerization of styrene, the coordination polymerization of conjugated dienes, the ring-opening polymerization of cyclic esters [18][19][20][21][22][23][24][25][26], and the coordination polymerization of polar monomers [27][28][29][30][31][32][33][34]. Yet, the employment of Ln-NHCs in this area remains relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%